Aspectos ético-jurídicos da responsabilidade civil do médico em prática liberal Civil responsibility of physicians in liberal practice context: ethical-juridical aspects - Paulo Antônio de Carvalho Fortes (Universidade de São Paulo, 1990)
É feita atualização de conceitos ético-jurídicos referentes à responsabilidade civil do trabalho médico efetuado em prática liberal. São analisados tópicos que norteiam a formação do vínculo contratual entre o médico e seu cliente assim como os princípios da noção de culpa, elemento básico da responsabilidade civil tanto para os atos técnicos quanto no domínio do humanismo médico. São destacadas soluções apresentadas para a questão, em sistemas jurídicos europeus. The ethical-juridical concepts related to the civil responsibility of medical activity in liberal practice are brought up to date. To this end, the arguments which guide the shaping up of the contractual relationship between the physician and the client are analysed, as also are the foundations on which the notion of guilt - an essential component of civil responsibility, whether relating to technical acts of to those within the field of medical humanism - are grounded. The answers presented for the solution of this question by European juridical systems are given.